2000
DOI: 10.1001/archderm.136.5.609
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Improves Psoriasis and Normalizes Models of Proliferative Skin Disease

Abstract: Background: Psoriasis is often treated with agents that activate nuclear hormone receptors for glucocorticoids, retinoids, and vitamin D. The peroxisome proliferatoractivated receptor-␥ (PPAR␥) is a related nuclear hormone receptor that can be activated by its ligands, including the thiazolidinediones.Objective: To assess whether treatment with troglitazone, a currently available thiazolidinedione used to treat diabetes mellitus, has an effect on psoriasis in normoglycemic patients and whether ligands for PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(66 citation statements)
references
References 48 publications
3
62
0
1
Order By: Relevance
“…PPARα expression was not detectable by this method, but was detectable by reverse transcriptase-polymerase chain reaction (RT-PCR) over time in culture. In addition, PPARγ (both γ1 and γ2) could be detected by RT-PCR after inducing keratinocyte differentiation by shifting to a high calcium medium, a finding which has been confirmed [33]. Remarkably, the specific ligand BRL did not cause reporter gene transactivation of endogenous PPARγ; the possibility that the culture medium was not optimal for keratinocyte differentiation during this experiment cannot be ruled out from the data.…”
Section: Ppar Gene Expression In Normal Skinsupporting
confidence: 56%
See 2 more Smart Citations
“…PPARα expression was not detectable by this method, but was detectable by reverse transcriptase-polymerase chain reaction (RT-PCR) over time in culture. In addition, PPARγ (both γ1 and γ2) could be detected by RT-PCR after inducing keratinocyte differentiation by shifting to a high calcium medium, a finding which has been confirmed [33]. Remarkably, the specific ligand BRL did not cause reporter gene transactivation of endogenous PPARγ; the possibility that the culture medium was not optimal for keratinocyte differentiation during this experiment cannot be ruled out from the data.…”
Section: Ppar Gene Expression In Normal Skinsupporting
confidence: 56%
“…PPARγ immunofluorescence was found in human keratinocytes cultured under differentiating conditions (high calcium medium) [33]. One preliminary study found immunohistochemical expression of all the PPAR subtypes in facial skin sections [34].…”
Section: Ppar Gene Expression In Normal Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CD36 in human keratinocytes is induced by treatment with ligands of each PPAR subtype. Administration of the formerly available PPARg agonist troglitazone to patients improved psoriasis and inhibited keratinocyte proliferation, suggesting that this class of drugs may be beneficial in treating diseases of the skin (64).…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
“…Induction of PPARα and PPARγ expression is linked to differentiation, and accordingly, is confined to suprabasal keratinocytes. PPARδ and PPARγ inhibition resulted in a dramatic decrease in proliferation and a robust up-regulation of the expression of involucrin and transglutaminase [104, 105]. Preliminary results have shown expression of PPARδ and PPARγ in the human sebaceous gland [106, 107].…”
Section: Biological Activity Of Hormones In Human Skinmentioning
confidence: 99%